Is there foul play in the leaf pocket? The metagenome of floating fern Azolla reveals endophytes that do not fix N2 but may denitrify. Issue 1 (30th October 2017) - Dijkhuizen, Laura W.; Brouwer, Paul; Bolhuis, Henk; Reichart, Gert‐Jan; Koppers, Nils; Huettel, Bruno; Bolger, Anthony M.; Li, Fay‐Wei; Cheng, Shifeng; Liu, Xin; Wong, Gane Ka‐Shu; Pryer, Kathleen; et al.
Summary: Dinitrogen fixation by Nostoc azollae residing in specialized leaf pockets supports prolific growth of the floating fern Azolla filiculoides . To evaluate contributions by further microorganisms, the A. filiculoides microbiome and nitrogen metabolism in bacteria persistently associated with Azolla ferns were characterized. A metagenomic approach was taken complemented by detection of N2 O released and nitrogen isotope determinations of fern biomass. Ribosomal RNA genes in sequenced DNA of natural ferns, their enriched leaf pockets and water filtrate from the surrounding ditch established that bacteria of A. filiculoides differed entirely from surrounding water and revealed species of the order Rhizobiales. Analyses of seven cultivated Azolla species confirmed persistent association with Rhizobiales. Two distinct nearly full‐length Rhizobiales genomes were identified in leaf‐pocket‐enriched samples from ditch grown A .  filiculoides . Their annotation revealed genes for denitrification but not N2 ‐fixation. 15 N2 incorporation was active in ferns with N. azollae but not in ferns without. N2 O was not detectably released from surface‐sterilized ferns with the Rhizobiales. N2 ‐fixing N. azollae, we conclude, dominated the microbiome of Azolla ferns. The persistent but less abundant heterotrophic Rhizobiales bacteria possibly contributed to lowering O2 levels in leaf pockets but did not release detectable amounts of the strong greenhouse gas N2 O.